Analysis and Design of CRC-32 IEEE 802.3 Generator for 8 Bit Data Using VHDL - Aprilia Putri Dewanty; Bheta Agus Wardijono (KILAT, 2022)
In the communication system to achieve better quality data transmission required a method that can detect errors and correct errors. Cyclic Redundancy Check (CRC) is one of the methods used to perform data transmission on data link layer that can detect errors. CRC-32 is used to error-checking on Ethernet or implemented to IEEE 802.3. CRC generator in this research use CRC-32 IEEE 802.3 with 8 bit data width. This research can be implemented in the field of Electrical Engineering, especially in the telecommunications section, namely Ethernet which functions for transfer files and data via a computer network. CRC here has a role to prevent data changes caused by noise during the transmission process. The methods used in this design is modulo-2 division parallel circuit. This design is expected to use a simple schematic circuit, less noise and less resources. Testing is done by matching result of simulation using Xilinx ISE Simulator with implementation on Spartan 3E XC3S500E device with result of count . This research requires a resource of 223 4-input LUTs, 114 Occupied slice, 72 IOB flip flops, 114 bonded IOBs and 1 BUFGMUXs, where this research obtained resources is fewer than with previous research